Consumption of Traditional Saudi Foods and Their Estimated Glycaemic Index and Glycaemic Load - Al-Mssallem, M.Q. (Pakistan Journal of Nutrition, 2018)
Background and Objective: The consumption of traditional foods has recently declined worldwide. This study aimed to evaluate the consumption of traditional Saudi foods and to estimate their glycaemic index and glycaemic load. Materials and Methods: A total of 480 Saudi females (aged 20.0±1.2 year) were recruited for the study. Height, weight and blood pressure were initially measured and body mass index was calculated. Additionally, the glycaemic index and glycaemic load of selected traditional Saudi foods were estimated. Results: The results revealed that the majority of students strongly believed that traditional Saudi foods are very healthy and nutritious, however, the average consumption of them was low. Moreover, there was a significant negative correlation between body mass index and the consumption of some individual foods, namely, Kabsa with Basmati and Hassawi rice. Results have shown that traditional Saudi foods, on average, had a low glycaemic index and a medium glycaemic load, with values of 55 and 12, respectively. Conclusion: It is concluded that traditional Saudi foods have a low estimated GI and GL, making them a good choice for losing and maintaining weight.